THE EFFECT OF PROBLEM BASED LEARNING ON CREATIVE THINKING SKILLS IN SIMPLE HARMONIC MATERIALS - Annisa Nisa Pasaribu; Winsyahputra Ritonga (UNIVERSITAS NEGERI MEDAN, 2020)
This study aims to determine the effect of the problem based learning (PBL) model on students' creative thinking skills in simple harmonic materials in the second semester X class of SMA Negeri 1 Batang Kuis. The research method used was quasi-experimental with the design of two group pre-test post-test. The population of this study was all class X IPA 4 as the experimental class applied PBL model and in class X IPA 3 as the control class applied a conventional model, each class as many as 32 students. The data of this study were obtained using an instrument in the form of an essay test consisting of a test of creative thinking skills, each amounting to 5 items that have been declared valid. Analysis can be done using normality, homogeneity, and hypothesis testing. The finding of the data analysis obtained the average posttest value of creative thinking skills experiment class 68.5 and the average value of the control class 59.18. The posttest data t test results There are significant differences in creative thinking skills between students who learn to use the PBL model and students who learn to use conventional models.Keywords: Creative Thinking Skills, Problem Based Learning, Simple Harmonic